All Days 1992
DOI: 10.2118/25054-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Gullfaks Field Development: Challenges and Perspectives

Abstract: The Gullfaks Field is located in the Norwegian Sector of the North Sea, block 34/10, and currently has the capability of producing more than 70,000 Sm3/d of oil (440,000 stb/d) from three CBS platforms. The reservoir sands comprise shallow marine to fluvial sediments of the Cook Formation, Statfjord Formation and Brent Group, ranging in age from Early to Middle Jurassic. Water injection is the major drive mechanism for maintaining reservoir pressure above bubble point. Development wells have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Nearshore‐marine and deltaic sandstones of the Middle Jurassic Brent Group constitute the main reservoirs of Gullfaks Field (Figs 1–4; Eriksen et al ., 1987; Petterson et al ., 1990, 1992; Olaussen et al ., 1992; Tollefsen et al ., 1992). The Brent Group comprises five formations, the upper four of which have been sampled in the present study (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nearshore‐marine and deltaic sandstones of the Middle Jurassic Brent Group constitute the main reservoirs of Gullfaks Field (Figs 1–4; Eriksen et al ., 1987; Petterson et al ., 1990, 1992; Olaussen et al ., 1992; Tollefsen et al ., 1992). The Brent Group comprises five formations, the upper four of which have been sampled in the present study (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Gullfaks field is one of Norway's largest oil fields located in block 34/10 along the western flank of the Viking Graben in the northern North Sea [1][2][3]. It is a structural complex with reservoirs in several strata, fragmented by numerous faults [4][5][6]. It was discovered in 1978 in the Tampen region of the North Sea; it was put into production in 1986 and reached peak production in 2001 [7][8][9].…”
Section: -Introductionmentioning
confidence: 99%
“…As soon as the Gullfaks field began production in 1986, a drop in production was noticed due to the depletion of the reservoir. After primary and secondary recovery carried out, it was observed that the reservoir still contained a considerable amount of hydrocarbons that could be exploited [5][6][7]. This made it possible to use assisted recovery techniques.…”
Section: -Introductionmentioning
confidence: 99%